Creativity in numbers: Uncovering students' potential through diagnostic learning evaluation at SMK Pasundan 4 Bandung - Ainil Kaafil Hasanah; Lulu Banusalam; Muhammad Rizqi Febrian (Curricula: Journal of Curriculum Development, 2024)
This article discusses the innovative application of diagnostic learning evaluation methods in SMK Pasundan 4 Bandung to uncover students' potential. This article outlines an approach focusing on utilizing technology, data analysis, and student engagement in the evaluation process. This research explores diagnostic methods to provide an overview of student understanding and explore students' creative skills and potential that have not yet been revealed. Data presentation uses a qualitative approach, employing the interactive analysis model, which involves several stages, including data selection, data presentation, and conclusion drawing. Additionally, we employ observation instruments, interviews, and documentary studies. This research shows that diagnostic learning evaluation with a creative approach can transform the learning paradigm at SMK Pasundan 4 Bandung. SMK Pasundan 4 Bandung can produce graduates ready to face the ever-changing business world by involving students in the evaluation process and harnessing modern technology.